Giant Nonlinear Optical Activity of Achiral Origin in Planar Metasurfaces with Quadratic and Cubic Nonlinearities. Issue 15 (23rd February 2016) - Chen, Shumei; Zeuner, Franziska; Weismann, Martin; Reineke, Bernhard; Li, Guixin; Valev, Ventsislav Kolev; Cheah, Kok Wai; Panoiu, Nicolae Coriolan; Zentgraf, Thomas; Zhang, Shuang
Abstract : 3D chirality is shown to be unnecessary for introducing strong circular dichroism for harmonic generations. Specifically, near‐unity circular dichroism for both second‐harmonic generation and third‐harmonic generations is demonstrated on suitably designed ultrathin plasmonic metasurfaces with only 2D planar chirality. The study opens up new routes for designing chip‐type biosensing platform, which may allow for highly sensitive detection of bio‐ and chemical molecules with weak chirality.